Another Option of Perforator Flap in the Lateral Thoracic Area: Lateral Thoracic Perforator Flap - Kim, Jeong Tae; Kim, Sang Wha (Journal of Reconstructive Microsurgery, 2014)
Background The lateral thoracic donor site provides two types of perforator flap; the latissimus dorsi perforator flap based on the musculocutaneous perforator, and the thoracodorsal perforator flap based on the septocutaneous perforators from the thoracodorsal artery. In this article, we introduce a direct cutaneous perforator derived from the lateral thoracic artery, which provides another option for harvesting a perforator flap from the lateral thoracic region.Patients and Methods Overall 17 patients underwent reconstructions using the lateral thoracic perforator flap for defects resulting from tumor-ablative surgery in the head and neck region, chronic osteomyelitis, and trauma or chronic wounds of the lower extremities.Results All flaps survived without major complications and six of the flaps were harvested in a chimeric pattern.Conclusion When the latissimus dorsi and thoracodorsal perforator flaps are not suitable, the lateral thoracic perforator flap provides another option from the lateral thoracic region that is useful for a variety of reconstructions. However, anatomic variation and the shorter and smaller pedicle compared with the thoracodorsal vessels are drawbacks of the lateral thoracic perforator flap that make it difficult to approach. The combination of the versatility of the previous two perforator flaps based on the thoracodorsal system and this additional type of lateral thoracic perforator flap makes the lateral thoracic region a universal donor site.
Keywords: free tissue flaps; perforator flap; thoracic arteries